2021
DOI: 10.1186/s12245-021-00389-y
|View full text |Cite
|
Sign up to set email alerts
|

A peculiar case of psychosis: anti-NMDAr encephalitis

Abstract: Background Psychosis in pregnancy is rare and could be life-threatening. It requires prompt evaluation and proper management accordingly. Anti-N-methyl-d-aspartate receptor (anti-NMDAr) encephalitis following herpes simplex virus (HSV) infection is a rare cause of psychosis during pregnancy. Case presentation A 20-year-old woman at 18 weeks gestation presented with agitation and a 3-day history of hallucinations. She had a prior hospitalization for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Vidarabine, an antiviral mainly used against herpes simplex virus, has been reported to improve a patient's schizo-affective disorder possibly induced by the viral infection as per a case study reported by Schlitt et al [91]. Associations of herpes simplex virus to schizophrenia have been found not only in the immediate viral carriers but also in their offspring [92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…Vidarabine, an antiviral mainly used against herpes simplex virus, has been reported to improve a patient's schizo-affective disorder possibly induced by the viral infection as per a case study reported by Schlitt et al [91]. Associations of herpes simplex virus to schizophrenia have been found not only in the immediate viral carriers but also in their offspring [92][93][94].…”
Section: Discussionmentioning
confidence: 99%